Effect of ionic liquids on kinetic parameters of dicyanate ester polycyclotrimerization and on thermal and viscoelastic properties of resulting cyanate ester resins - A. Fainleib; O. Grigoryeva; A. Vashchuk; O. Starostenko; S. Rogalsky; A. Rios de Anda; T-T-T. Nguyen; D. Grande (eXPRESS Polymer Letters)
A strong catalytic effect of 1.0 wt% ionic liquids (ILs) on kinetic parameters of dicyanate ester of bisphenol E(DCBE) polycyclotrimerization was evidenced, and structure-property relationships of resulting densely cross-linked cyanate ester resins (CERs) were investigated. Three different ILs with contrasted reactivity were employed as a catalysts: an aprotic IL, i.e. 1-octyl-3-methyl imidazolium tetrafluoroborate ([OMIm][BF4]), a protic IL, i.e. 2-(hydroxyethylamino) imidazolinium chloride ([HEAIm][Cl]), and a protic polymeric IL, i.e. poly(hexamethylene guanidine) toluene sulfonate ([PHMG][TS]). Both [HEAIm][Cl] and [PHMG][TS] were reactive towards DCBE monomer, whereas [OMIm][BF4] was chemically inert, as confirmed by Fourier Transform Infrared (FTIR) spectroscopy. Noticeably, the conversion (αc) of cyanate groups in the presence of ILs dramatically increased, and a significant dependence of αc values on IL chemical structure was found. The corresponding mechanisms of DCBE polycyclotrimerization in the presence of different ILs were proposed. All the CER/IL networks exhibited a high thermal stability inherent to neat CER, as shown by TGA, whereas unexpected significant changes of the viscoelastic characteristics for CER/IL networks compared to pure CER analogue were observed using DMTA.